The use of ethanol as contrast enhancer in synchrotron X-ray phase-contrast imaging leads to heterogeneous myocardial tissue shrinkage: a case report - Gabriel Bernardino; Àngels Calvet-Mirabent; Hector Dejea; Eduard Guasch; Anne Bonnin; Patricia Garcia-Canadilla (Journal of Synchrotron Radiation)
One of the main limitations of conventional absorption-based X-ray micro-computed tomography imaging of biological samples is the low inherent X-ray contrast of soft tissue. To overcome this limitation, the use of ethanol as contrast agent has been proposed to enhance image contrast of soft tissues through dehydration. Some authors have shown that ethanol shrinks and hardens the tissue too much, also causing small tissue ruptures due to fast dehydration. However, the local tissue deformation occurring as a consequence of tissue dehydration and whether tissue shrinkage can modify myocardial architecture has not been quantified yet. The aim of this paper is to quantify the local myocardial tissue deformation due to ethanol dehydration based on 3D non-rigid registration and perform a detailed characterization of its myocardial tissue organization, before and after ethanol dehydration. A rat adult heart was imaged with synchrotron-radiation-based X-ray phase contrast imaging (X-PCI) three times: before, 9 h after and 342 h after ethanol immersion. The total volume shrinkage as well as changes in the left ventricular myocardial thickness were computed. Then, to determine local deformation of the heart caused by ethanol dehydration, the related 3D tomographic datasets were registered by means of a non-rigid registration algorithm. Finally, changes on the orientation and organization of myocytes were assessed. Our results show that the use of ethanol in synchrotron X-PCI can improve image contrast, but the tissue shrinkage is not homogeneous thus changing the local myocardial organization.